Duodenal bulb tumour of unknown origin - Hankiewicz-Ziołkowska, Karolina; Soboń, Marcin; Szylberg, Tadeusz; Rudziński, Janusz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Gastrointestinal stromal tumours (GIST) are rare mesenchymal neoplasms of the gastrointestinal tract. Their development typically depends on mutations in the Kit or PDGFRA gene. We have diagnosed and treated a duodenal bulb GIST in a 63-year-old woman. The confirmation of the diagnosis was made on the basis of a histological test after radical resection of the tumour. Making the right diagnosis is crucial for patients, since complex surgical and pharmacological approaches are effective even in the advanced stages of the disease. Nevertheless, radical surgical treatment is still the primary choice for patients with GIST.